Effect of light-curing units on push-out fiber post bond strength in root canal dentin - Calixto, L. R.; Bandéca, M. C.; Silva, F. B.; Rastelli, Alessandra Nara de Souza [UNESP]; Porto-Neto, S. T.; Andrade, M. F. (Pleiades Publishing, 2009)
The purpose of this study was to evaluate the effectiveness of different light-curing units on the bond strength (push-out) of glass fiber posts in the different thirds of the root (cervical, middle and apical) with different adhesive luting resin systems (dual-cure total-etch; dual-cured and self-etch bonding system; and dual-cure self-adhesive cements), Disks of the samples (n = 144) were used, with approximately 1 mm of thickness of 48 bovine roots restored with glass fiber posts, that were luted with resin cements photo-activated by halogen LCU (QTH, Optilux 501) and blue LED (Ultraled), with power densities of 600 and 550 mW/cm 2, respectively. A universal testing machine (MTS 810 Material Test System) was used with a 1 mm diameter steel rod at cross-head speed of 0.5 mm/min until post extrusion, with load cell of 50 kg, for evaluation of the push-out strength in the different thirds of each sample. The push-out strength values in kgf were converted to MPa and analyzed through Analysis of Variance and Tukey's test, at significance level of 5%. The results showed that there were no statistical differences between the QTH and LED LCUs. The self-adhesive resin cement had lower values of retention. The total-etch and self-adhesive system resin cements seem to be a possible alternative for glass fiber posts cementation into the radicular canal and the LED LCU can be applied as an alternative to halogen light on photo-activation of dual-cured resin cements. © 2009 Pleiades Publishing, Ltd.
Keywords: Blue LEDs; Bond strength; Bonding systems; Crosshead speed; Dual-cure; Fiber posts; Light-curing units; Load cells; Luting resins; Material test system; Photo-activated; Power densities; Push-out; Resin cement; Root canals; Self-adhesive; Self-etch; Statistical differences; Steel rod; Strength values; Universal testing machines; Bond strength (materials); Cell membranes; Cements; Curing; Fibers; Glass fibers; Hydraulic structures; Light transmission; Load testing; Regression analysis; Resins; Steel testing; Glass bonding